Impact of the Booming Online Selling Industry on Business Owners of The Fashion Industry Physical Stores in Teodoro Arcenas Trade Center, Roxas City - Santos, Jelly Grace L. Delos; Ostia, Heaven Leigh N. Dela (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This study examines the impact of the booming online selling industry on fashion business owners operating physical stores at Teodoro Arcenas Trade Center, Roxas City. It explores the demographic profile of respondents, including sex, age, civil status, estimated monthly profit, and educational attainment. Findings reveal a dominance of females, younger age groups, single status, lower income, and high school educational attainment among respondents. The results indicate that the booming online selling industry has extremely affected the number of customers and the monthly profit of business owners of the physical store's fashion industry in Teodoro Arcenas Trade Center, Roxas City. This also indicates that the booming online selling industry has severely affected the manpower of business owners of the physical store's fashion industry in Teodoro Arcenas Trade Center, Roxas City. However, there is no significant difference in the impact of online selling based on sex, age, civil status, estimated profit, or educational attainment. This implies that these factors do not play a significant role in determining the impact of the online selling industry on physical stores in the fashion industry at the Teodoro Arcenas Trade Center, Roxas City.